Cross Cultural Translation and Translatability of Poetry - Anjum, Rehana Yasmin (Advances in Social Sciences Research Journal, 2016)
Translation is as old as human history. We can get access to the culture as well as literature of other nations through the channel. Translation is a very creative skill, but its modes differ according to the purposes it has to serve. Translating literature of any other language makes heavy demands on the translator. Literary translation is one of the types of translation. Translation of poetry has been a chimera for the translators since ages. Due to its unique structure and appeal, translatability of poetry has been a hot issue of translation studies. This issue becomes even severe when a ST and TT are from different socio-cultural backgrounds. Poetry is highly creative genre where poet’s personal lexicon plays an important role. Translating poetic diction and personal lexicon of the poets across cultures is a herculean task. This paper aims at analyzing the problems in dealing with this task, especially in symbolic poetry. The purpose of the study is to analyze the quality of translation by various translators on the basis of the degree of translatability, that how far these translations are accurate in depicting the poet‘s message more effectively on lexical and thematic levels.Poly system theory of Evan Zohar and Toury has provided the theoretical background. The study has three independent variables; translations by different translators (having different Socio-cultural background).Lexical and syntactic choices and Treatment of allusions. (Pragmatic awareness about the poet and the poem).There is one dependent variable; Truthful Translation nearer to the original thought. Translation Quality Assessment (TQA) Model that applies socio-semiotic approach developed by Julianne House (1976) is used. It is found that not all types of poetry are difficult to translate, but some highly symbolic or subjective types are difficult only in the absence of proper socio-pragmatic knowledge. It will also help further researchers to analyze the problems faced in order to maintain the standard of equivalence, reliability, and entertainment in translated work that is drawn out of a great piece of original art.